ATOPIC DERMATITIS: FROM MOLECULAR SPECIFICITY OF ORAL MANIFESTATIONS TO CLINICAL IMPLICATIONS - Petronela Bărgăoanu; Doinița Temelie-Olinici; Ana-Emanuela Botez; Ionuț Cătălin Botezatu; Carmen Elena Cotrutz (Romanian Society of Oral Rehabilitation, 2022)
Atopic dermatitis (AD) is considered a systemic disease that also manifests itself in the oral cavity. The presence of oral pathologies in patients with atopic dermatitis can result in the worsening of the atopic disease, and on the other hand, the presence of AD can favour the development of oral diseases. As changes in the expression of AD-specific molecules can be observed in AD patients both in the skin and in the oral mucosa, the investigation of the expression levels of some salivary molecules could be possible biomarkers of risk for the onset, diagnosis and progression of the disease. The evolution of lesions diagnosed in patients with atopic dermatitis can be significantly improved by early and correct treatment of infectious odontogenic foci.